Plasminogen Activators and Plasminogen Activator Inhibitors in Liver Deficiencies Caused by Chronic Alcoholism or Infectious Hepatitis - Tran-Thang, Chiên; Fasel-Felley, Josette; Pralong, Gerard; Hofstetter, Jean-René; Bachmann, Fedor; Kruithof, Egbert K O (Thrombosis and Haemostasis, 1989)
Plasma concentrations of tissue-type plasminogen activator (t-PA), urokinase (u-PA), plasminogen activator inhibitor 1 (PAI-1) and PAI-2 were studied in 53 patients with liver deficiency caused by chronic alcoholism (n = 40), viral hepatitis (n = 10) or malignant disease of the liver (n = 3) and compared to that of a control group (n = 20) of healthy subjects. u-PA and PAI-1 levels were significantly increased in all patients with chronic alcoholism, whereas high t-PA was only observed in combination with disturbed liver function tests or with liver cirrhosis (two and sixfold above control values, respectively). A good correlation was observed between t-PA and gamma glutamyl transferase (r = 0.615; p <0.001). In patients with infectious hepatitis or with malignant disease of the liver t-PA was normal whereas u-PA and PAI-1 were increased.PAI-2 levels were close to or below the detection limit (15 ng/ml) in the control group and in most patients. However, in two patients with alcohol induced cirrhosis PAI-2 levels were approximately 45 ng/ml and in one patient with hepatocarcinoma even 66 ng/ml. Thus, in liver disease, marked elevations of t-PA, u-PA and PAI-1 levels may occur, with increased PAI-1 as an early marker of liver defects and t-PA a marker of severe liver defects.
Keywords: Liver disease; Cirrhosis; Plasminogen activator; Plasminogen activator inhibitor; Fibrinolysis